HISTÓRIA E CULTURA AFRICANA E AFRO-BRASILEIRA NO CONTEXTO DA EDUCAÇÃO INFANTIL EM BREVES, MARAJÓ-PA - GUIOMAR, Jessica Leão (2025)
This study has as its object the theme “História e Cultura Africana e Afro-brasileira” in the context of Early Childhood Education in Breves, Estado do Pará. It is guided by the following questions: The theme “história e cultura africana e afro-brasileira” is present in the Municipal Curriculum Matrix for Early Childhood Education, Curriculum Proposal and Pedagogical Policy Project for early childhood education schools in the city of Breves? How is this issue addressed in these documents? Is there a difference or similarity in the approach to this theme in the aforementioned documents? The general objective was to identify whether the subject under study is included in the documents that guide this level of education in the city of Breves. Specifically, we seek to know how these documents present/address a história e cultura dos povos africanos e afro-brasileiros. We also verified similarities and differences between the way of approaching the referred theme adopted by the cited documents. In the theoretical field, we have the contribution of Vital Didonet (2001), Priscila Freitas (2016), Lucineide Soares (2013), Almeida e Sanches (2016), Silvia Costa (2017), among others. This is a documental research whose documents analyzed were: The Municipal Curriculum Matrix of Early Childhood Education, a Curriculum Proposal; seven Political Pedagogical Projects and four teaching plans at the kindergarten schools in the city Breves. Among the results obtained, it is noteworthy that the municipality's early childhood education curriculum includes the following generating themes: Cultura afro-brasileira e Diversidade étnica e cultural, which dialogue with our study theme. Schools have the autonomy to choose and develop one of the generating themes, but only three PPPs mention étnico-raciais relations. This perspective is also not identified in the only Curriculum Proposal analyzed, as in the teaching plans, we found that all analyzed schools included the theme in their plans. We conclude that the kindergarten schools in Breves, although they do not work on the topic at hand in depth in their curriculum, develop work that contributes to combating racial prejudice and promoting the appreciation of the cultura e história de povos africanos e afro-brasileiros.